As easy as ABC: evaluation of safe sleep initiative on safe sleep compliance in a freestanding pediatric hospital - Traci Leong; Manon Billaud; Maneesha Agarwal; Terri Miller; Terri McFadden; Jonathan Johnson; Sarah Gard Lazarus (BMC, 2019)
Abstract Background The American Academy of Pediatrics (AAP) recommends the ABCs of safe infant sleep (alone, back, clear crib) to combat the increasing rates of Sudden Unexplained Infant Death (SUID). It is unclear if these recommendations are followed for infants hospitalized in pediatric facilities after the newborn period. The objectives of this study were to assess baseline infant sleep behaviors at a tertiary care freestanding pediatric hospital and to evaluate the effectiveness of a hospital-based infant safe sleep program in improving adherence to safe sleep recommendations. Methods A quality improvement program with pre- and post- analyses was performed on a convenience sample of infants < 12-months old utilizing a crib audit tool on two general pediatric inpatient units. The crib audit tool was used before and after the safe sleep program intervention. It recorded the infant's sleep position, location during sleep, and sleep environment. Interventions included: 1) nursing education, 2) crib cards with a checklist of the ABC's of safe sleep provided for the cribs of hospitalized infants, and 3) tracking boards to report weekly measured compliance with the ABCs. Chi square analysis was used to compare adherence to recommendations before and after program implementation. Results There were 62 cribs included pre-intervention and 90 cribs post-intervention. Overall, there was no significant change in safe sleep positioning (81% to 82%, p = 0.97). There was a significant increase in adherence to the safe sleep environment recommendation (3% to 38%, p < 0.01). Overall safe sleep, including both position and environment, referred to as ABC compliance, improved from 3% pre-intervention to 34% post-intervention (p < 0.01). Only 18% of cribs audited displayed a crib card, demonstrating poor compliance on placement of the cards. There was no significant difference in compliance with safe sleep recommendations between infants with a crib card compared to those without (25% vs. 37%, p = 0.51). Conclusions Significant improvements were made in sleep environments and overall safe sleep compliance after introduction of crib cards and tracking boards. Most likely the crib auditing process itself and the tracking boards had a larger impact than the crib cards.